Experienced violence processes for trans* people in educational institutions - Polak, Roberta; Guimarães, Rafael Siqueira de; Cruz, Gilmar Carvalho (Revista Hipótese, 2016)
This article deals with experienced violence cases for trans * people in educational institutions. We conducted a qualitative research, in which five trans * people were interviewed, from the perspective of narrative analysis. Through this study it was possible to see school history permeated by exclusions and silences, which makes us reflect on how the binary gender norms violate lives that escape socio-cultural gender norms.